Recycled concrete chloride ion resistant penetrant used in high chlorine salt field, and preparation method and application thereof

By using LDHs/nano-silica sol composite materials as anti-chlorine ion penetration agent in recycled concrete, the problems of concrete reinforcement corrosion and shortage of building materials in high-chlorine salt environments are solved, and the effect of significantly improving the anti-chlorine ion penetration performance and extending service life is achieved.

CN119683890APending Publication Date: 2025-03-25CHANGZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411861030.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing technology still has shortcomings in improving the anti-corrosion and seepage resistance of offshore concrete, especially in high chloride salt environments, concrete reinforcement is still severely corroded, and over-exploitation of natural sand and gravel has led to a shortage of building materials.

Method used

LDHs/nano-silica sol composite material is used as the anti-chlorine ion penetration agent for regenerated concrete. By adsorbing a large amount of chloride ions, thinning ITZ, enhancing matrix density and anti-chlorine ion permeability, it effectively blocks the erosion of chloride ions.

Benefits of technology

It significantly improves the anti-chlorine ion permeability of recycled concrete, extends its service life, and shows good corrosion resistance in high chloride salt environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683890A_ABST
    Figure CN119683890A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of building material regeneration, in particular to a recycled concrete chloride ion resistant penetrant used in the field of high chlorine salt, and a preparation method and application of the recycled concrete chloride ion resistant penetrant. The recycled concrete chloride ion resistant penetrant used in the high chlorine salt field is formed by compounding LDHs and nano silica sol, and preferably, the nano silica sol has relatively small influence on LDHs nucleation and grain growth and has relatively good dispersity on LDHs. The chlorine immobilizing agent has a good chlorine immobilizing effect in a simulated recycled concrete solution in a marine environment, and the chloride ion immobilizing amount can reach 74mg / g; meanwhile, the composite system has a more remarkable effect of improving the performance of the recycled aggregate in the recycled concrete, a good chloride ion improving effect can be achieved when the doping amount of the composite system is 1.0 wt% of that of Portland cement, and the chloride ion diffusion coefficient of the composite system is reduced by 26.6% compared with that of a blank group. The recycled concrete chloride ion resistant penetrant applied to the field of high chlorine salt has important value in the field of recycled concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building material recycling, in particular to a recycled concrete chloride ion penetration-resistant agent for use in high chloride salt fields, and a preparation method and application thereof. Background Art

[0002] The marine environment is complex and changeable. Marine concrete structures are subject to a variety of physical and chemical attacks in this environment. - Steel bar corrosion caused by corrosive ions, led by ions, is considered to be the key cause of the deterioration of the durability of marine concrete. After penetrating the surface of concrete, they react electrochemically with the surface of the steel bar, causing the steel bar to rust. The volume of the corroded steel bar expands 4 to 10 times, generating internal stress, causing the concrete to crack and accelerate its deterioration process. Steel bar corrosion not only reduces the cross-section of the steel bar, but also weakens the adhesion between the steel bar and the cement-based material, significantly reducing the overall bearing capacity and durability of the concrete structure. Under the action of long-term corrosion, the porous and heterogeneous marine concrete structure weakens, resulting in spalling and stratification of the surface concrete. Therefore, it is necessary to improve the anti-corrosion and anti-seepage capabilities of marine concrete.

[0003] In the existing technology, the specific measures taken to improve the anti-corrosion and anti-seepage capabilities of marine engineering concrete can be divided into "active corrosion protection" and "passive corrosion protection". Among them, there is currently no clear standard for "active corrosion protection" to test the treatment results of this method, and the size of the protection potential depends on factors such as pH value, chloride ion content, cement composition or type, and the actual situation is more complicated.

[0004] "Passive corrosion protection" mainly starts from the outside to directly block, inhibit or delay the corrosion of chloride ions on concrete, so that chloride ions cannot contact the steel bars and protect the steel bars. The methods of "passive corrosion protection" are: ① Concrete surface coating, applying epoxy resin, polyurethane, acrylate, super hydrophobic coating, fluorocarbon coating (solvent-based or water-based), modified acrylic coating, mineral coating and polyurethane-epoxy composite coating on the concrete surface to block or delay corrosion; ② Concrete body, by adding high-performance aggregates (high-performance crushed stone, high-performance fly ash), changing the type of cementitious materials (sulfoaluminate cement, chloride-resistant cement, ferroaluminate cement and composite cement, etc.), controlling the water-cement ratio (reducing the water-cement ratio, etc.), adding external components (nanomaterials Materials, mineral admixtures, chloride ion curing agents and fibers, etc.) enhance the density of the concrete body or solidify more chloride ions to achieve the effect of inhibiting and slowing down the penetration of chloride ions; ③ Steel bar surface corrosion protection is divided into two categories: one is a single coating, which relies on a single material or technology to provide corrosion protection, such as epoxy resin, polyurethane, enamel and galvanizing. These coatings are usually simple and easy to use, but their long-term corrosion resistance and durability in specific environments are limited; the other is a composite coating, which enhances performance by combining multiple materials or technologies, such as nano-composite coatings, metal-based composite coatings and functional composite coatings.

[0005] Although the above-mentioned anti-corrosion and anti-seepage methods have improved the anti-seepage property of concrete, they still cannot meet the actual needs, and the corrosion of concrete reinforcement is still serious.

[0006] In addition, the over-exploitation of natural sand and gravel as fine aggregates for concrete has caused a shortage of concrete raw materials and a surge in construction costs. In response to the government's policy on recycling construction waste, reducing the negative impact of excessive sand and gravel exploitation and storage of construction waste on the environment, and achieving healthy development of the construction industry, the development of recycled concrete using construction waste is the most effective way to solve this dilemma. Therefore, as a new type of building material, recycled fine aggregate has gradually become an ideal substitute for river sand with its advantages of wide sources, stable performance, environmental protection and energy saving.

[0007] Therefore, it is of great value and significance to adopt more effective methods to improve the chloride ion permeability resistance of recycled concrete in high chloride salt areas. Summary of the invention

[0008] The technical problem to be solved by the present invention is to overcome the deficiencies in the prior art and provide a recycled concrete chloride ion penetrant for use in the high chloride salt field and a preparation method and application thereof. The recycled concrete chloride ion penetrant of the present invention can not only adsorb a large amount of chloride ions in recycled concrete for marine engineering, but also thin ITZ, enhance matrix compactness and chloride ion permeability resistance, effectively block, inhibit or delay chloride ion erosion in recycled concrete, and greatly increase the service life of recycled concrete.

[0009] The technical solution adopted by the present invention to solve its technical problem is:

[0010] A recycled concrete chloride ion penetration agent for use in high chloride salt fields. The recycled concrete chloride ion penetration agent is a LDHs (layered double hydroxide) / nano silica sol composite material, wherein the molar ratio of LDHs to nano silica sol is 1: (0.05-0.3), preferably 5:1.

[0011] Furthermore, the silica particle size in the nano-silica sol is 30nm, the solid content of the nano-silica sol is 30%, and the pH value of the nano-silica sol is 10.8. The nano-silica sol does not destroy the crystallinity and peak value of LDHs, and can exist stably in the solution, and can also regulate the morphology of LDHs to form a highly dispersed single-layer structure.

[0012] A method for preparing the above-mentioned recycled concrete anti-chloride ion penetrant for use in high chloride salt fields specifically comprises the following steps:

[0013] Step S1, mixing calcium nitrate, aluminum nitrate and ferric nitrate in a molar ratio of Ca:Fe:A1=10:1:4 and stirring evenly, which is recorded as solution A; mixing sodium nitrate and sodium hydroxide and stirring evenly, which is recorded as solution B;

[0014] Step S2, adding solution A and solution B dropwise into the three-necked flask while stirring continuously, and continuing to stir evenly after all the additions are completed;

[0015] Step S3, after the dropwise addition is completed, the obtained mixed solution and the beaker are sealed and placed in a forced air drying oven to carry out a crystal growth reaction of LDHs, i.e., LDHs crystallization, to obtain an LDHs solution;

[0016] Step S4: After the LDHs solution is cooled, nano-silica sol is added and stirred to obtain a reaction solution. The reaction solution is then centrifuged several times until neutral, and then dried at 100° C. and ground into powder to obtain a finished product for use as a chloride ion penetrant for recycled concrete in high chloride salt fields.

[0017] Furthermore, in step S1, the molar ratio of calcium nitrate, ferric nitrate, aluminum nitrate, sodium nitrate and sodium hydroxide is (20-40): (2-4): (8-16): (1-5): (30-50).

[0018] Furthermore, in step S3, the crystallization temperature is 80-100°C, and the crystallization time is 18-36h. When the crystallization temperature is within this range, LDHs with good crystal form and sharp peaks can be obtained; and when the crystallization time is within this range, the crystal morphology is good, and it is a micro-nano two-dimensional hexagonal layered structure. If the crystallization time is short, the morphology is irregular, and if the crystallization time is long, the crystal is large and is not conducive to the dense filling effect in cement concrete, so this range has the best effect.

[0019] Furthermore, in step S4, the molar ratio of the LDHs solution to the nano-silica sol is 1: (0.05-0.3), preferably 5: 1. The LDHs / nano-silica sol composite material synthesized within this range can give full play to the regulating effect of the nano-silica sol on LDHs, and has little effect on the nucleation and grain growth of LDHs; the negatively charged nano-silica sol will partially adhere to the upper surface of the positively charged LDHs and between the two layers, thereby improving the dispersibility of LDHs and enhancing the surface adsorption and ion exchange function of LDHs to chloride ions.

[0020] An application of the above-mentioned recycled concrete chloride ion penetration agent for high chloride salt fields is to mix the recycled concrete chloride ion penetration agent into the recycled concrete, the recycled concrete includes silicate cement, recycled fine aggregate, water and water reducing agent, and the amount of the recycled concrete chloride ion penetration agent added is 0.5-3.0wt% of the silicate cement.

[0021] Furthermore, the mass ratio of the silicate cement, recycled fine aggregate, water and water reducing agent is 1:(1.2-1.5):(0.23-0.26):(0.003-0.008), preferably 1:1.2:0.23:0.005.

[0022] The beneficial effects of the present invention are as follows: the present invention is reasonably designed and has the following advantages:

[0023] (1) The anti-chloride ion penetration agent for recycled concrete in the high chloride salt field of the present invention is composed of LDHs and nano-silica sol; the silica particle size in the nano-silica sol is 30nm, the solid content of the nano-silica sol is 30%, and the pH value of the nano-silica sol is 10.8; the nano-silica sol has high adaptability to LDHs, has little effect on the nucleation and grain growth of LDHs, and has a sharp LDHs crystal peak in XRD;

[0024] (2) The high-chloride salt field recycled concrete anti-chloride ion penetration agent of the present invention has a good chloride ion curing effect in the simulated high-chloride salt recycled concrete pore solution, and its maximum chloride ion curing amount can reach 74 mg / g, showing a good chloride ion curing effect; the high chloride ion curing effect is mainly due to the fact that the nano-silica sol can regulate the LDHs structure to form a single-layer structure, which is more conducive to the surface adsorption and ion exchange of LDHs; at the same time, the nano-silica sol can also react with substances such as calcium hydroxide in the pore solution (SiO2·nH2O+Ca(OH)2→CSH(xCaO·SiO2·yH2O) to generate CSH with chloride ion surface adsorption function, and the chloride ion adsorption of the solid composite system is further improved, and the two have a synergistic effect;

[0025] (3) The high chloride salt field recycled concrete anti-chloride ion penetration agent of the present invention is used in recycled concrete. Recycled concrete uses recycled fine aggregate instead of river sand or machine-made sand. As a new type of building material, recycled fine aggregate has the advantages of wide source, stable performance, environmental protection and energy saving, and has gradually become an ideal substitute for river sand. Recycled fine aggregate has good anti-chloride ion erosion advantages when used in a high chloride salt environment. This is because the surface of the crushed recycled aggregate usually has more rough textures and microporous structures. This unique characteristic helps to increase the physical adsorption capacity of chloride ions in the recycled concrete matrix, thereby inhibiting the transmission and diffusion of chloride ions. At the same time, the fine dust in the recycled aggregate can react with the strong calcium oxide in cement hydration to generate a denser CSH gel (from loose type to dense type), thereby blocking the pores and preventing the entry of chloride ions.

[0026] (4) The anti-chloride ion permeation agent for recycled concrete in the high chloride salt field of the present invention can significantly improve the anti-chloride ion permeation performance of recycled concrete. When the dosage of the anti-chloride ion permeation agent for recycled concrete is 1.0wt.% (Example 11), the chloride ion diffusion coefficient of the recycled concrete is as low as 9.06×10 -12 m 2 / s, which is 26.6% lower than that of the blank group (Example 9), showing a good anti-chloride ion diffusion effect; this is mainly due to the unique advantages of the composite system in recycled concrete. The nano-silica sol in the composite system can participate in cement hydration and react with the large-sized calcium hydroxide in the interface transition zone of the recycled concrete to generate CSH gel, which reduces the side wall effect and unilateral growth effect of the interface transition zone; secondly, LDHs can fill the pores in the interface transition zone of the recycled concrete and compact its structure. At the same time, it can also adsorb certain harmful ions and reduce the migration product and deposition effect of ions in the interface transition zone; finally, the preferred nano-can better regulate the LDHs structure to form a highly dispersed thin layer structure, further improve the density of the matrix, and thin the interface transition zone, thereby reducing the chloride ion permeability of the recycled concrete matrix. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 It is the XRD test diagram of the finished products obtained in Example 1 to Example 8;

[0029] Figure 2 These are recycled concrete samples with different admixture amounts;

[0030] Figure 3 These are the 28-day chloride ion diffusion coefficient test results of the samples prepared in Examples 9 to 14. DETAILED DESCRIPTION

[0031] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0032] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this description, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0033] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Example 1

[0035] A method for preparing a chloride ion-resistant penetrant for recycled concrete in a high chloride salt field, comprising the following steps:

[0036] Step S1, calcium nitrate, aluminum nitrate and ferric nitrate are mixed together in a molar ratio of Ca:Fe:A1=10:1:4 and placed in a magnetic stirring device for stirring for 10 minutes, which is recorded as solution A; sodium nitrate and sodium hydroxide are mixed together and magnetically stirred for 10 minutes, which is recorded as solution B;

[0037] Step S2, adding solution A and solution B dropwise into a three-necked flask while stirring continuously, and after all the additions are completed, continue magnetic stirring for 2 hours;

[0038] Step S3, after the dropwise addition is completed, the obtained mixed solution and the beaker are sealed and placed in a forced air drying oven to carry out a crystal growth reaction of LDHs, i.e., LDHs crystallization, the crystallization temperature is 80° C., the crystallization time is 24 h, and an LDHs solution is obtained;

[0039] Step S4: After the LDHs solution is cooled, a nano-silica modifier (containing 2 g of active ingredient) is added and stirred to obtain a reaction solution. The reaction solution is then centrifuged several times until neutral, dried at 100° C., and ground into powder to obtain a finished product.

[0040] In this embodiment, the molar ratio of calcium nitrate, ferric nitrate, aluminum nitrate, sodium nitrate, sodium hydroxide and nano-silica sol is 20:2:8:1:30:0.2.

[0041] In step S4 of this embodiment, the nano-silicon dioxide modifier is nano-silicon dioxide modified powder, specifically VK-SP30 produced by Xuancheng Jingrui New Materials Co., Ltd.

[0042] Example 2

[0043] The difference from Example 1 is that in step S4 of this example, the nano-silicon dioxide modifier is nano-silicon dioxide modified powder, specifically VK-SP30H produced by Xuancheng Jingrui New Materials Co., Ltd.

[0044] Example 3

[0045] The difference from Example 1 is that in step S4 of this example, the nano-silica modifier is nano-silica sol, specifically VK-S01W produced by Xuancheng Jingrui New Materials Co., Ltd.

[0046] Example 4

[0047] The difference from Example 1 is that in step S4 of this example, the nano-silica modifier is nano-silica sol, specifically VK-S01A produced by Xuancheng Jingrui New Materials Co., Ltd.

[0048] Example 5

[0049] The difference from Example 1 is that in step S4 of this embodiment, the nano-silicon dioxide modifier is nano-silica sol, specifically JN-40-M30 produced by Shandong Yinfeng Nano New Materials Co., Ltd.

[0050] Example 6

[0051] The difference from Example 1 is that in step S4 of this example, the nano-silica modifier is nano-silica sol, specifically VK-S01B produced by Xuancheng Jingrui New Materials Co., Ltd.

[0052] Example 7

[0053] The difference from Example 1 is that in step S4 of this example, the nano-silicon dioxide modifier is nano-silicon dioxide modified powder, specifically VK-SP15 produced by Xuancheng Jingrui New Materials Co., Ltd.

[0054] Example 8

[0055] The difference from Example 1 is that in step S4 of this embodiment, the nano-silicon dioxide modifier is nano-silica sol, specifically JN-40-M100 produced by Shandong Yinfeng Nano New Materials Co., Ltd.

[0056] The specific preparation processes of Examples 1 to 8 can be found in Table 1.

[0057] Table 1 Preparation process of Example 1 to Example 8

[0058]

[0059] Performance Testing

[0060] 1. The finished products obtained in Examples 1 to 8 were subjected to XRD tests respectively, and the results are as follows: Figure 1 shown. Figure 1 It can be seen that the crystal structure of LDHs synthesized in Example 6 is the most complete, and the crystal form is sharp. The VK-S01B nano-silica sol (30nm) used in this method has little effect on its nucleation and grain growth, and the negatively charged VK-S01B nano-silica sol is more likely to partially adhere to the surface of LDHs and between the two layers, thereby improving the dispersibility of LDHs. Furthermore, compared with 10nm and 100nm silica sols, 30nm nano-silica sol has been proven to have higher dense filling effect and resistance to chloride ion permeability in the field of concrete. It is better than 10nm silica sol because the specific surface area of ​​30nm particles is relatively large, which is not conducive to agglomeration, while the dense filling effect of 100nm silica sol is not significant.

[0061] 2. Test the chloride ion curing amount of the composite system in a simulated solution

[0062] (1) According to the American Society for Testing and Materials standard "ASTM D1141-98" simulated seawater solution, the chloride ion concentration in the seawater solution is 0.55 mol / L, which is slightly higher than the chloride ion content in the seawater in the eastern coastal areas of my country, the South China Sea, the Yellow Sea and the Bohai Sea. - , SO4 2- , HCO3 - ,Mg 2+ , Ca 2+ , Na + , K + The elements in each sea area are similar to those in our solution, so the solution we prepared is typical. This solution is marked as A and is reserved for future use.

[0063] (2) Take 500g of silicate cement and place it in a NJ-160A cement slurry mixer with a water-cement ratio of 0.6 and stir it evenly. Then seal it for 60 minutes, then take the upper liquid and centrifuge it at a speed of 5000r / min. Finally, filter it through a 0.45 micron semipermeable membrane. The solution is marked as B and set aside.

[0064] According to the SL 352-2006 "Hydraulic Concrete Test Procedure", the ion selective electrode method was used to determine the free chloride ion content in the simulated solution at room temperature. The model is DCCL-816 chloride ion concentration meter; measurement range: 1.0×10 -5 ~1.0×10 -1 mol / L; measurement time: 3min. 1g of recycled concrete anti-chloride ion penetrant for high chloride salt fields (prepared in Example 6), or 1g of unmodified LDHs, or 1g of nano-silica sol was added to the mixed solution, and the total amount of the solution taken was 60ml. A1 to A5 are recycled concrete anti-chloride ion penetrants added to different reaction solutions. The specific formulas and test results are shown in Table 2.

[0065] Table 2 The amount of chloride ions solidified by the composite system after adsorption-desorption equilibrium

[0066]

[0067]

[0068] It can be concluded from Table 2 that in the simulated marine concrete solution, in the mixed solution prepared by the method proposed in the present invention, in the A1 solution, the adsorption amount of chloride ions by the recycled concrete anti-chloride ion penetrant (i.e., LDHs and nano-silica sol composite system) is the highest, reaching 74 mg / g. In the mixed solutions of A2 to A5 formulas, the adsorption amount of chloride ions by the recycled concrete anti-chloride ion penetrant is less than that of A1 because the chloride ion concentration in the mixed solutions of A2 to A5 formulas is lower than that of A1, and high concentration of chloride ions is more conducive to the adsorption of chloride ions by the recycled concrete anti-chloride ion penetrant. From the two comparative examples A6 and A7, it can be seen that the adsorption of chloride ions per unit mass of unmodified LDHs and nano-silica sol is significantly smaller than that of the composite system, which also shows that the chloride ion solidification effect of the modified composite system is significant. The main reason is that the nano-silica sol in the modified composite system can regulate the structure of LDHs to form a single-layer structure, which is more conducive to the surface adsorption and ion exchange of LDHs and adsorb more chloride ions. At the same time, the nano-silica sol in the modified composite system can also react with calcium hydroxide and other substances in the pore solution (SiO2·nH2O+Ca(OH)2→CSH(xCaO·SiO2·yH2O) to generate CSH with chloride ion surface adsorption function, and the chloride ion adsorption of the solid composite system is further improved. The two have a synergistic effect.

[0069] 3. Test on the chloride ion impermeability of concrete

[0070] The recycled concrete chloride ion anti-penetrating agent prepared in Example 1 was mixed into the recycled concrete and the performance was tested.

[0071] The recycled concrete is C50 concrete, which is composed of 1000g of silicate cement, 1200g of recycled fine aggregate, 5g of water reducer and 230g of water. The recycled fine aggregate is obtained by crushing and screening from a decoration waste production base in Changzhou. The fineness modulus of the recycled fine aggregate is 2.52%, the crushing value is 30.98%, and the apparent density is 2460kg / m 3 , water absorption rate is 4.0%, the price is only 18 yuan / t, which is only 1 / 5 of natural aggregate; recycled fine aggregate has high crushing value and water absorption rate, and low apparent density. The performance of its fine aggregate is inferior to that of natural fine aggregate, but it has its own unique advantages, low price, and the above-mentioned construction solid waste belongs to the advantage of resource utilization.

[0072] Preparation method: ① Weigh the materials of each component according to the proportion; ② Pour the silicate cement and recycled fine aggregate into the mixer and stir evenly; ③ Add the polycarboxylate water reducer into the water and stir evenly by magnetic force; Add different amounts of LDHs and nano-silica sol composite system to the above mixed aqueous solution, and ultrasonicate for 5 minutes; ④ Add the above mixed solution to the powder and continue to stir evenly by magnetic force, and prepare and cure the sample according to the "GB / T50081-2019" standard for 28 days, and use the obtained sample for the chloride ion penetration resistance test. Figure 2 .

[0073] The amount of chloride ion penetration inhibitor added to the recycled concrete in Examples 9 to 14 (i.e., the mass percentage of the chloride ion penetration inhibitor in the recycled concrete to the silicate cement) is shown in Table 3.

[0074] Table 3 The amount of addition of Example 9 to Example 14

[0075] Example Incorporation amount Example 9 0 Example 10 0.5 Embodiment 11 1.0 Example 12 1.5 Example 13 2.0 Embodiment 14 3.0

[0076] According to the relevant provisions of the Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete (GB / T50082-2009), the 28-day chloride ion diffusion coefficients of the samples prepared in Examples 9 to 14 were measured respectively. The test results are shown in Figure 3 .

[0077] Depend on Figure 3 It can be seen that in the chloride ion diffusion coefficient experiment of 28-day concrete samples, from Examples 9 to 14 (the amount of chloride ion penetration agent added to the recycled concrete is between 0% and 3%, respectively), it can be seen that within a certain range, with the continuous increase in the amount of LDHs and nano-silica sol chloride ion penetration agent, the chloride ion permeability resistance in the recycled concrete mortar gradually decreases. In Example 11, the chloride ion diffusion coefficient of the recycled concrete can reach a minimum of 9.06×10 -12 m 2 / s, the chloride ion diffusion depth is 10.5mm, which is 26.6% lower than that of the blank sample (Example 9). Among them, the anti-chloride ion penetrant works as follows: the micro-nano-scale LDHs and nano-silica sol composite system has unique advantages in recycled concrete, and the composite system can fill the pores of recycled concrete; at the same time, it can also weaken the interface transition zone (ITZ) of concrete. Its mechanism is mainly as follows: first, the nano-silica sol in the composite system can participate in cement hydration, react with the large-sized calcium hydroxide in the ITZ area, generate CSH gel, and reduce the side wall effect and unilateral growth effect of ITZ; second, LDHs can fill the pores in the ITZ area to compact its structure, and at the same time can also adsorb certain harmful ions (such as Cl - ,CO3 2- , SO4 2-), reducing the migration and deposition of ions in the ITZ area; thirdly, nano-silica sol can regulate the LDHs structure to form a highly dispersed thin layer structure, further improving the density of the matrix and thinning the ITZ. Furthermore, the use of recycled aggregates in marine buildings shows unique advantages in resisting chloride ion corrosion. This is because the surface of the crushed recycled aggregates usually has more rough textures and microporous structures. This unique characteristic helps to increase the physical adsorption capacity of chloride ions in the concrete matrix, thereby inhibiting the transmission and diffusion of chloride ions. At the same time, the fine dust in the recycled aggregate can react with cement hydration to form a denser CSH gel, thereby blocking the pores and preventing the entry of chloride ions. It solves the problem that it is difficult to fully balance the solid chlorine rust prevention, strength and density of traditional cement concrete.

[0078] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A chloride ion penetrant for recycled concrete used in high chloride salt fields, characterized in that: The recycled concrete anti-chloride ion penetration agent is a LDHs / nano-silica sol composite material, wherein the molar ratio of LDHs to nano-silica sol is 1:(0.05-0.3).

2. The method for preparing the chloride ion-resistant penetrant for recycled concrete in high chloride salt fields according to claim 1, characterized in that: The diameter of silicon dioxide particles in the nano-silica sol is 30 nm, the solid content of the nano-silica sol is 30%, and the pH value of the nano-silica sol is 10.

8.

3. A method for preparing a chloride ion penetrant for recycled concrete used in high chloride salt fields according to claim 1 or 2, characterized in that: The specific steps include: Step S1, mixing calcium nitrate, aluminum nitrate and ferric nitrate in a molar ratio of Ca:Fe:A1=10:1:4 and stirring evenly, which is recorded as solution A; mixing sodium nitrate and sodium hydroxide and stirring evenly, which is recorded as solution B; Step S2, adding solution A and solution B dropwise into the three-necked flask while stirring continuously, and continuing to stir evenly after all the additions are completed; Step S3, after the dropwise addition is completed, the mixed solution and the beaker are sealed and placed in a forced air drying oven to carry out a crystal growth reaction of LDHs, i.e., LDHs crystallization, to obtain an LDHs solution; Step S4: After the LDHs solution is cooled, nano-silica sol is added and stirred to obtain a reaction solution. The reaction solution is then centrifuged several times until neutral, and then dried at 100° C. and ground into powder to obtain a finished product for use as a chloride ion penetrant for recycled concrete in high chloride salt fields.

4. The method for preparing a chloride ion penetrant for recycled concrete in high chloride salt fields according to claim 3, characterized in that: In step S1, the molar ratio of calcium nitrate, ferric nitrate, aluminum nitrate, sodium nitrate and sodium hydroxide is (20-40): (2-4): (8-16): (1-5): (30-50).

5. The method for preparing a chloride ion penetrant for recycled concrete in high chloride salt fields according to claim 3, characterized in that: In the step S3, the crystallization temperature is 80-100° C., and the crystallization time is 18-36 hours.

6. The method for preparing a chloride ion penetrant for recycled concrete in high chloride salt fields according to claim 3, characterized in that: In the step S4, the molar ratio of the LDHs solution to the nano-silica sol is 1:(0.05-0.3).

7. An application of the chloride ion penetrant-resistant recycled concrete in high chloride salt fields as claimed in claim 1 or 2, characterized in that: The recycled concrete anti-chloride ion penetration agent is mixed into the recycled concrete, which comprises silicate cement, recycled fine aggregate, water and a water reducing agent, and the amount of the recycled concrete anti-chloride ion penetration agent added is 0.5-3.0wt% of the silicate cement.

8. The use of the chloride ion penetrant-resistant agent for recycled concrete in high chloride salt fields according to claim 7, characterized in that: The mass ratio of the silicate cement, recycled fine aggregate, water and water reducing agent is 1: (1.2-1.5): (0.23-0.26): (0.003-0.008).

Citation Information

Patent Citations

  • Multifunctional admixture for improving concrete strength and efficiently inhibiting chlorine ion diffusion and steel bar corrosion, and preparation method thereof

    CN112374783A

  • Preparation method and application method of efficient chloride ion curing agent for sea sand mortar

    CN116891358A